A steady-state analysis method for optimal operation of dividing-wall column. (2nd November 2018) - Luo, Junwen; Xu, Chunjian; Zhang, Yawen; Yan, Kaixin; Zhu, Jesse
Highlights: Whether the optimal operation of dividing-wall column (DWC) can be realized without adjusting vapor split ratio can be determined. For ternary separation, dilution effect in DWC is proposed. It reveals DWC may need online optimization. Feedback is used for the online optimization of DWC. The relation between degree of closeness (between energy consumption ( Q ) and Q min ) and setpoint range of manipulated variable/control variable can be acquired. Disturbance and implementation error can be handled by using the proposed method. Abstract: Optimal operation indicates energy consumption ( Q ) close to its Q min while product specifications are satisfied. Generally, for DWC, there are two manipulated variables (MVs) to keep Q close to Q min . Therefore, there are three operation mode, which are two MVs online optimization (Mode 2), single MV online optimization (Mode 1) and two MVs fixed (Mode 0). A steady-state analysis method for optimal operation of DWC with disturbance is presented. In the method, whether optimal operation can be achieved under Mode 0/ Mode 1 can be determined. Feedback is used for the online optimization under Mode 1 and Mode 2. The relation between degree of closeness (between Q and Q min ) and setpoint range of manipulated variable/control variable can be acquired. For ternary separation, dilution effect in DWC is proposed. It reveals DWC may need online optimization. Implementation error is discussed. Disturbance and implementation error can be handled by using the proposed method simultaneously. The important ternary separation of benzene, toluene, and o-xylene in industry is used as an example to illustrate the method. In the case, optimal operation can be realized under Mode 1 and Mode 2.